2018
DOI: 10.5093/jwop2018a4
|View full text |Cite
|
Sign up to set email alerts
|

Moderated Mediation between Work Life Balance and Employee Job Performance: The Role of Psychological Wellbeing and Satisfaction with Coworkers

Abstract: In response to growing health and productivity problems resulting from employees' lack of work-life balance, many organizations are taking serious steps to reduce conflict in their employees' work and family roles (Fapohunda, 2014; Working Families, 2017). This has led to increasing researchers' and managers' interest in this area of study. Organizations not permitting work-life flexibility tend to negatively impact their employees' job performance, whereas enhancing work-life balance may benefit both employee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 59 publications
6
60
0
3
Order By: Relevance
“…flexibility in working hours and supportive supervision) and employee job performance. ISSN 2162-3058 2019 These findings support previous studies by Mendis and Meerakkody (2017) and Haider et al (2017) which revealed that the better WLB practices will improve employee job performance and satisfaction. The mediation analysis also demonstrated that, in terms of explanatory power, the inclusion of job satisfaction in step 2 explained 30.0% of the variance in the dependent variable (job performance).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…flexibility in working hours and supportive supervision) and employee job performance. ISSN 2162-3058 2019 These findings support previous studies by Mendis and Meerakkody (2017) and Haider et al (2017) which revealed that the better WLB practices will improve employee job performance and satisfaction. The mediation analysis also demonstrated that, in terms of explanatory power, the inclusion of job satisfaction in step 2 explained 30.0% of the variance in the dependent variable (job performance).…”
Section: Discussionsupporting
confidence: 86%
“…H2: There is a significant relationship between supportive supervision and job performance Haider et al (2017) studied the influence of psychological well-being and satisfaction in the relationship between WLB and employee job performance. Their study suggested that psychological well-being mediates the relationship between WLB and job performance.…”
Section: The Development Of Research Hypotheses and Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…PLS-SEM estimates were obtained from the latest version of SmartPLS 3 (3.2.7) software (Ringle, Wende, & Becker, 2015). The PLS approach to SEM is a component based procedure of estimation with iterative algorithms of least squares regressions (Haider, Fernandez-Ortiz, & de Pablos Heredero, 2017;Haider, Jabeen, & Ahmad, 2018;Hair, Hult, Ringle, & Sarstedt, 2014). Hypotheses are tested based on resampling method-bootstrapping.…”
Section: Analytical Approachmentioning
confidence: 99%
“…Work-life balance is a concept gaining accelerated importance and realization amongst individuals (Bouzari & Karatepe, 2020;Kelliher et al, 2019;Barber et al, 2019). Work-life balance has a significant role in boost quality of work (Bhende et al, 2020), satisfaction, and psychological well-being (Haider et al, 2018), employee commitment (Hofmann & Stokburger-Sauer, 2017), social life (Ola et al, 2019) and so forth. Importantly, scholars have identified the scarcity of research on the topic of work-life balance (e.g., Haar et al, 2019) whereby, limited studies have attempted to investigate how to predict WLB during the times of crisis such as COVID-19 Pandemic.…”
Section: Work-life Balancementioning
confidence: 99%